Loss of ARID1A-Associated Protein Expression is a Frequent Event in Clear Cell and Endometrioid Ovarian Cancers. Issue 1 (1st January 2012) - Lowery, William J.; Schildkraut, Joellen M.; Akushevich, Liudmila; Bentley, Rex; Marks, Jeffrey R.; Huntsman, David; Berchuck, Andrew
Abstract : Background: Inactivating somatic mutations in the ARID1A gene are described in a significant fraction of clear cell and endometrioid ovarian cancers leading to loss of the corresponding protein (BAF250a). Expression of BAF250a was examined in clear cell and endometrioid cancers accrued as part of the North Carolina Ovarian Cancer Study, a population-based case-control study, to determine whether loss of expression is associated with clinical and epidemiological features. Methods: Immunostaining for BAF250a was performed using 212 clear cell and endometrioid ovarian cancers. Associations between loss of BAF250a and clinical and epidemiological features were examined. Variables were analyzed by logistic regression. Results: Loss of BAF250a expression was noted in 96 (45%) of 212 cancers: 34 (41%) of 82 clear cell cases and 62 (48%) of 130 endometrioid cases. There was no relationship between the loss of BAF250a and stage, grade, survival, or epidemiological variables. Conclusions: These data confirm that loss of the ARID1A-encoded protein BAF250a is a frequent event in the genesis of clear cell and endometrioid ovarian cancers. Loss of BAF250a was not associated with clinical or epidemiologic characteristics. One explanation for these findings is that inactivation of the chromatin remodeling pathway may be a requisite event in the development of these cancers.